Parthian Coins from Kampyrtepa - Gorin, Aleksei (Anabasis. Studia Classica et Orientalia, 2010)
The ancient settlement of Kampyrtepa (“Hill of the Old Lady” in Uzbek) is situated 30 km south-west of the town of Termez, downstream the Amu Darya River. The history of Kampytepa’s exploration is 30 years old. The Parthian period of the history of the settlement is the least explored. The discovery of coins of allegedly Parthian origin called for distinguishing it as a separate phase. In various publications their number varies from 6 to 12. These publications leave a number of questions still unsolved, including the attribution of the types and the issue and circulation dates. This calls for having a closer look at the Parthian coins from Kampyrtepa.